Ethnic-sensitive social work practice - Devore, Wynetta; Schlesinger, Elfreide G. (Columbus : Charles E. Merrill Publishing Company, 1981)
This book is about ethnicity, social class, and social work practice. It was written because for many years we worried about the fact that knowledge about the life-styles and needs of different class and ethnic groups was not sufficiently integrated into principles and methods of social work practice.
Part I. Conceptual formulations -- Part II. Ethnic-sensitive practice.
Keywords: SOCIAL WORK